Effective Versions of Two Theorems of RADO. (17th March 2020) - Bell, Jason; Funk, Daryl; Du Kim, Byoung; Mayhew, Dillon
Abstract: Let $M$ be a representable matroid on $n$ elements. We give bounds, in terms of $n$, on the least positive characteristic and smallest field over which $M$ is representable.